Textos em língua inglesa como sementes de uma experiência vivida por alunos de ensino médio em uma Escola Pública Estadual - Simone, Sandra Harumi Shiokawa de (2014)
This research has the target of describing and interpreting the phenomenon reading of texts in English taken from three different sources by High School students from a public state school, with the aims of confronting the view that students have about reading texts in English with the teacher s view; considering what the learners think learning is; and understanding the way they really read in English. To reach these purposes, the following research question was asked: What is involved in the experience of reading texts in English taken from three different sources by High School students from a state public school? The methodology used in this investigation was the Hermeneutic-Phenomenological Approach (FREIRE, 2006, 2007, 2010, 2012), and the corpus of this research was composed by the texts produced by the students when they answered the following questions suggested after the reading of each text in English: (a) Describe the experience of reading a text taken from a textbook/ a specialized magazine/ a North-American magazine; (b) What have you learned with/from the text?; (c) Which strategies have you used to understand the text? The theoretical background of this study was the perspective of Complexity, based on Morin (1982/1990, 1990/2001, 2000, 2003), Capra (1996), Moraes (1996/2012), and Mariotti (2007); the topics related to reading and its development were grounded on Freire P. (1981/2006), Koch & Elias (2006), Rojo (2009), Santaella (2012), Grabe & Stoller (2011), Nardi (2010), and on the Official Documents: Lei de Diretrizes e Bases (BRASIL,1996), Parâmetros Curriculares Nacionais - Língua Estrangeira (BRASIL, 1998) e Parâmetros Curriculares Nacionais Ensino Médio (BRASIL,1999). The themes that emerged from the interpretation of the students´ texts showed a positive change of attitude regarding reading in English after their participation in this research, because they discovered their own potential, which they had not noticed until then. That fact provoked a rupture in their beliefs for they did not know or were not convinced they had enough knowledge to read texts in English. The themes also showed that the awareness of their potential for learning increased their self stem, promoting more confidence in themselves and in the quality of the teaching offered for them, besides their participation in the decisions related to their classes, leading the teacher to a reflection about the her attitude as a professional and a human being